Effectiveness of procurement contracts management in achieving value for money in procurement of works: A case of Moshi University College of Cooperative and Business Studies (MUCCoBS) - Mchopa, Alban (Mzumbe University, 2024)
A Dissertation submitted to the School of Business in partial fulfilment of the requirements for Award of the Master of Science in Procurement and Supply Chain Management (MSc. PSCM) of Mzumbe University, 2013